การสร้างสรรค์ผลิตภัณฑ์หัตถกรรมจากภูมิปัญญาท้องถิ่นของผู้สูงอายุเพื่อรองรับการท่องเที่ยว อำเภอเชียงแสน จังหวัดเชียงราย - มะโนวัง, จิราพร; วังตาล, ชญานิน; นิคม, อภิเดช (Area Based Development Research Journal, 2018)
The purposes of this research were to study local wisdom applied in the production of handmade products, basketry and handwoven items; and to collaborate with the local elderly group in the production process to serve the tourism of Chiang Saen district, Chiang Rai province. The data were obtained from 20 local experts in handmade products, basketry and hand-woven products from Wiang Sub-district Municipality and Wiang Chiang Saen sub-district, Chiang Saen district, Chiang Rai province. The research instruments were in-depth-interview, forum, and product and package design. The results were as follows: regarding the local wisdom of handmade products, basketry and handwoven items, most elderly created handmade products for home appliances in their free time. The original basketry was meant to serve everyday living and most handmade pieces were not delicate but simple in design, such as a basket, a cone-shaped cover and a steaming pot. As for the famous fabric in Phra That Pha Ngao Temple, there were stories behind the patterns, and the meaning of the colors. Most hand-woven products were used for sarong pieces, shawls and bags. The researchers collaborated with the locals in community to analyze and suggest ways to improve the products as well as broadening the markets to fit tourists’ needs as follows. 1) The experts provided information about the revenue and marketing management and encouraged the community to use local materials and find low-cost quality materials to make good quality products for tourism purposes. 2) The traditional hand-woven fabric piece was originally priced 600 baht without packaging. It was suggested that this product could increase in value by improving the package, that is, adding historical details of the products, local tradition, culture and unique fabric patterns, and pricing it at 850 baht. The tourists were satisfied with the products and bought them back home as souvenirs while the elderly received more income every month.